2019
DOI: 10.1002/hep4.1334
|View full text |Cite
|
Sign up to set email alerts
|

Medication‐Related Problems in Outpatients With Decompensated Cirrhosis: Opportunities for Harm Prevention

Abstract: People with decompensated cirrhosis are often prescribed a complex regimen of therapeutic and prophylactic medications. In other chronic diseases, polypharmacy increases the risk of medication misadventure and medication‐related problems (MRPs), with associated increased morbidity, mortality, and health care costs. This study examined MRPs in a cohort of ambulatory patients with a history of decompensated cirrhosis who were enrolled in a randomized controlled trial of a pharmacist‐led, patient‐oriented medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(90 citation statements)
references
References 30 publications
3
87
0
Order By: Relevance
“…Medication‐related problems are very common in patients with cirrhosis. A recent single‐centre trial showed that more than half of medication‐related problems could be resolved by a pharmacist‐led medication review . These results are promising and the guidance we developed can support pharmacists.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Medication‐related problems are very common in patients with cirrhosis. A recent single‐centre trial showed that more than half of medication‐related problems could be resolved by a pharmacist‐led medication review . These results are promising and the guidance we developed can support pharmacists.…”
Section: Discussionmentioning
confidence: 82%
“…A recent single-centre trial showed that more than half of medication-related problems could be resolved by a pharmacist-led medication review. 5 These results are promising and the guidance we developed can support pharmacists. However, for large-scale implementation of pharmacists-led medication reviews in these patients, there are still some barriers to overcome as we demonstrated in this study.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 87%
See 2 more Smart Citations
“…Until now, no such intervention studies have been performed in patients with cirrhosis. (6) In this issue of Hepatology Communications, Hayward and colleagues (7) discuss the results of their randomized controlled trial of pharmacist-led, patientoriented, medication education intervention and its association between MRPs and patient outcomes. They documented at least two or more MRPs for all patients, with a median of 6 MRPs per patient.…”
Section: See Article On Page 620mentioning
confidence: 99%